The Effects of Biased Labor Market Expectations on Consumption, Wealth Inequality, and Welfare - Almut Balleer; Georg Duernecker; Susanne K. Forstner; Johannes Goensch (Center for Economic Studies and ifo Institute (CESifo), 2021)
Idiosyncratic labor risk is a prevalent phenomenon with important implications for individual choices. In labor market research it is commonly assumed that agents have rational expectations and therefore correctly assess the risk they face in the labor market. We analyse survey data for the U.S. and document a substantial optimistic bias of households in their subjective expectations about future labor market transitions. Furthermore, we analyze the heterogeneity in the bias across different demographic groups and we find that high-school graduates tend to be strongly over-optimistic about their labor market prospects, whereas college graduates have rather precise beliefs. In the context of a quantitative heterogenous agents life cycle model we show that the optimistic bias has a quantitatively sizable negative effect on the life cycle allocation of income, consumption and wealth and implies a substantial loss in individual welfare compared to the allocation under full information. Moreover, we establish that the heterogeneity in the bias leads to pronounced differences in the accumulation of assets across individuals, and is thereby a quantitatively important driver of inequality in wealth.
Keywords: E21; D84; 330; subjective expectations; labor markets; consumption; asset accumulation; wealth inequality